Question

( x^{4}-x^{3}+x^{2}+2 )
( =left(x^{4}right)^{2}-xleft(x^{2}right)+x^{2}+2 )
( =(2 x-2)^{2}-x(2 x-2)+(2 x-2)+2 quadleft{begin{array}{l}x^{2}+2=2 x Rightarrow x^{2}=2 x-2end{array}right] )
( =4 x^{2}-8 x+4-2 x^{2}+2 x+2 x-5+2 )
( 2 x^{2}-4 x+4 )
( =2left(x^{2}-2 x+2right) cdotleft[x^{2}+2=2 x rightarrow x^{2}+2-2 x=0right] )
2(0)
( = )
( =0 )
a) 0 is wrect ( [A m D] )
the peeriom mistake Sary for the This to is the

# If x² + 2 = 2x, then the value of x - x + x² + 2 is (A) O (C)-1 (D) VE (B) 1

Solution